Beyond Administrative Criteria: The Patterns of the Recognition of Quality in the Humanities - Kirtiklis, Kęstas; Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2022)
The present article seeks to discern the criteria or the quality of research, formulated and accepted within the scholarly community of the humanities. We argue that the scholars implicitly use these criteria opposing administrative evaluation. The analysis of these criteria revealed that they might be summarized in three broad categories – the novelty (originality, innovativeness) of the research; the excellence of the researcher (ability to conduct and describe the research); and the impact (academic as well as social-political). We argue that relevant criteria for the administrative evaluation of research in the humanities should draw on these perspectives.
Keywords: humanities; quality of research; novelty; excellence; impact